Knowledge, Attitude, and Compliance with Hypertension Patients at The Manggis I Karangasem Health Centre - Oktayanti, Leny; Widowati, I Gusti Ayu Rai; Tunas, I Ketut; Wintariani, Ni Putu (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2024)
High blood pressure or hypertension is a serious medical condition that significantly increases the risk of heart, brain, kidney, and other organ diseases. Most people with hypertension do not show specific symptoms and remain in good condition to perform routine activities. This study aimed to evaluate the knowledge, attitude, and compliance of hypertensive patients. A cross-sectional observational study was conducted at Puskesmas Manggis I Karangasem from March to May 2023 using a validated questionnaire. Data were analyzed using SPSS software version 25.0. A total of 120 respondents participated (100% response rate). Most of respondents were >65 years old (37.5%); male (61.7%); had secondary education (65.8%); not working (28.3%); had grade 1 hypertension (70.8%), and had no comorbidities (80.8%). Patient knowledge was categorized as good (109 [90.8%]), attitude was positive (75 [62.5%]), and medication compliance was high (79 [65.9%]). The results of the chi-square test showed that there was a significant relationship between knowledge and compliance (p-value=0.002), and there was a significant relationship between attitude and compliance (p-value=0.006). Knowledge and attitudes of hypertensive patients must continue to be improved so that patients comply to their medication therapy. Pharmacists are advised to conduct counseling on lifestyle, dietary patterns, and information related to complications in hypertensive patients.